Sacred canopies or religious markets? The effect of county-level religious diversity on later changes in religious involvement - Olson, Daniel V. A. (2020)
Secularization theories, such as Berger's Sacred Canopy argument, hold that religious diversity leads to a decline in religious participation. Religious market models (e.g., Finke and Stark) argue the opposite. Voas, Olson, and Crockett found that nearly all of the vast research exploring this important question prior to 2002 was flawed due to a previously unrecognized noncausal statistical relationship between measures of religious diversity and measures of religious participation. Since 2002, this methodological issue has largely stymied research on this important topic. We first describe how, following Voas et al.’s recommendations, longitudinal models can overcome these problems. We then apply these methods to data measuring the religious composition of all U.S. counties found in the Religious Congregations and Membership Studies from 1980, 1990, 2000, and 2010. Using multilevel longitudinal regression models, we find that greater county-level religious diversity is followed by later declines in county-level religious participation rates. The negative effect size of religious diversity is large and robust to changes in the control variables and different methods of measuring religious diversity.